DINAMIKA TAREKAT SYATHARIYAH DI MINANGKABAU TAHUN 1960-2021 - Sirajul Uhad; Herwandi Herwandi; Mhd Nur (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This journal examines the dynamics of the Syathariyah congregation in Minangkabau in 1960-2021. The aspects studied here are emphasized on religious understanding and practice, as well as the network of syathariya scholars in Minangkabau. In the development of the Syathariyah order in Minangkabau, there are differences in understanding, namely Wahdatul Wujud and Wahdatus Syuhud. Relying on historical methods (heuristics, criticism, interpretation, historiography), this study shows that, first, the teachings and religious practices of the Syathariyah congregation in Minangkabau underwent changes and additions, such as the practice of burha prayer. Second, there was an uprooting of the understanding of embodiment in Minangkabau, the understanding that developed was the Wahdatus Syuhud notion not Wahdatul Wujud. Third, the influence of a murshid is very strong in the community. In the relation of power, it can be seen that the dominance of the lord or murshid is more prominent, because in the field a murshid is a place for asking questions for the community. This thesis refutes the works which state that the teachings of the Syathariyah tarekat that developed in Minangkabau are Wahdatul Wujud teachings, whose ideas hinder progress, and are not dynamic. In this study, it is shown that Syathariyah's teachings are not extreme, which equates khaliq with makhluq. This research is in line with the opinion of Azyumardi Azra and Fazlur Rahman who stated that the tarekat showed their dynamism and were able to survive the demands of a very complex era.